2018
DOI: 10.3130/aije.83.1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Mental Healthcare Effect Using Plants Installation in Office Space

Abstract: Some offices have indoor environmental quality related problems such as space, indoor air quality, office workers' thermal comfort, productivity and mental stress. The objective of this study is to examine the effect of indoor plants on physiological/psychological responses and productivity, and to demonstrate the mental healthcare for office workers. In order to clarify the effect of indoor plants, we conducted a demonstration experiment in two rooms of an office. As a result, it was possible to confirm that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Elderly patients can reduce their functional decline with the presence of decorative plants (Berg et al, 2021). Especially in mental hospitals in Japan, the presence of decorative plants significantly reduces stress and increases work productivity for health workers (Genjo et al, 2018).…”
Section: Worker Responsementioning
confidence: 99%
“…Elderly patients can reduce their functional decline with the presence of decorative plants (Berg et al, 2021). Especially in mental hospitals in Japan, the presence of decorative plants significantly reduces stress and increases work productivity for health workers (Genjo et al, 2018).…”
Section: Worker Responsementioning
confidence: 99%
“…Iwasaki et al 10 examined the effect of various methods of installing ornamental plants on office desks on the subjective and psychological evaluations of workers and found that placing foliage plants on the desks of workers increased workplace environmental satisfaction. Genjo et al 11 examined the effects of indoor plants, installed in two offices, on the physiological and psychological reactions and productivity of humans, and confirmed the ameliorative effect of indoor plants on subjective visual fatigue and feelings of drowsiness. Sanchez et al 12 confirmed an improvement in the task performance of creative work and reduction of the mental workload when both daylight and greenery were introduced.…”
Section: Introductionmentioning
confidence: 96%
“…1.1 研究背景 自然との接触による人間の健康性やウェルビーイングの向上効果 1-3) や、生理的なストレスや精神的な疲労の軽減効果 4) が既往研究に より認められている。近年では、都市での生活による気分障害や不 安障害の増加が指摘されており 5) 、その要因の一つとして自然との 接触の不足が関係している可能性がある。建築分野でも利用者の健 康性への関心の高まりの中で、植物や昼光などの自然の要素を建築 環境に導入するバイオフィリックデザイン [6][7][8][9] が注目を集めている。 WELL 10) 、LEED 11) 、CASBEE Wellness Office 12) などの建築環境認 証制度にも自然へのアクセスに関連した評価項目が設けられており、 建築環境に自然を組み込む事例は今後も多く計画されると考えられ る。 したがって、 個々の建築の敷地や用途などの文脈を考慮しつつ、 建築環境へ自然の要素を効果的に計画する手法に関する知見が求め られる。 外部に自然が少ない都市部の建築の室内オフィス空間では、窓か らの昼光と空への眺望や、鉢やプランターを用いた屋内緑化、内装 への自然素材の利用などが自然との接触の方法として考えられる。 窓からの眺望の効果は広範に研究されており、特に窓を介した自然 への眺望による生理的ストレスの軽減 [13][14][15] やウェルビーイングの向 上 16,17) 、環境満足度や認知機能の改善 18) などが報告されている。屋 内植物が在室者に与える効果についても研究例は多く、実際のオフ ィスでのアンケート調査や介入実験により、屋内緑化による執務者 の主観的な生産性 19,20) 、ウェルビーイング 19) 、主観的な集中力と職 場への満足度 20) の向上や、 視覚疲労や自覚症状の緩和 21) 22,23) や、Reading span test で測定した注意力の改善 24) などが報告されている。 一方で、室内での植物の配置方法の違いが在室者に与える効果に 関する研究は少ない。橋本ら 25,26) は模擬執務空間で緑視率を段階的 に変えた際の心理・生理的効果を検証し、被験者の座席のレイアウ トにより緑視率の影響が変わる可能性 25) や、3.1%の緑視率で心理・ 生理的効果が最大になる 26) ことを報告した。 長谷川ら 27) は窓にカー テンを引いた会議室で実験を行い、植物の大きさごとにその印象が 向上する被験者との距離が異なることを報告した。しかし、これら の実験はいずれも、窓の有無など植物を設置する空間の特徴による 影響は分析していない。また、窓と屋内植物のような複数の自然要 素への曝露の効果を検証した研究例も限られており 28,29) Soma SUGANO, Miku TAZAKI, Mayumi OHBA, Shusuke TAKAHASHI, and Shin-ichi TANABE…”
unclassified